Determinantes del emprendimiento juvenil en Colombia: Un análisis desde la nueva economía institucional; Determinants of youth entrepreneurship in Colombia: An analysis from the new institutional economy - Marcela Torres M.; José Luis Ramos Ruiz; Moisés M. Galvis M.; José L. Ramos C; Juan E. Biswell J. (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2021)
– The purpose of this article is to determine the factors involved in the entrepreneurship of Colombian young people and to estimate the impact that these determinants have on the probability that a young person decides to be an entrepreneur. For the above, a probabilistic logistic model fed with the Global Entrepreneurship Monitor Colombia - 2019 database is estimated. The results show that informal factors such as self-confidence, reference frames and education level positively influence the probability of undertaking, a fact that shows that these informal conditions expressed by North (1993a) are key to influencing entrepreneurship by young people in Colombia. Finally, we conclude that the variables of fear of failure, constituted as informal conditioning factors, may not be seen as a barrier that influences the probability of entry of young Colombians into entrepreneurial activities.
Keywords: M10; M13; M21; M29; 330; entrepreneurship; institutions; youth